Salt - Moskowitz, Hannah (San Francisco : Chronicle Books, 2018)
Even though their parents disappeared during a hunt three months ago, seventeen-year-old Indi and his siblings Beleza, Oscar, and Zulu continue to roam the Mediterranean on their sailboat and hunt down monsters--but Indi yearns for a more settled life for his family and he hopes that his parents' journal with its tantalizing hints of a treasure will provide them all with the means of escape from their nomadic and dangerous life before it is too late.
Keywords: Treasure troves -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Families -- Juvenile fiction; Siblings -- Fiction; Buried treasure -- Fiction; Family life -- Mediterranean Region -- Fiction; Mediterranean Sea -- Juvenile fiction; Mediterranean Region -- Juvenile fiction; Mediterranean Sea -- Fiction; Mediterranean Region -- Fiction